Binding as an A’-phenomenon?: Some remarks from Turkish - Meral, Hasan Mesut (IBERIA: An International Journal of Theoretical Linguistics, 2014)
This article argues against the morpheme specificity of Binding Theory conditions in terms of pronoun-anaphor complementarity and proposes a tripartite system for the language at issue, Turkish. Focusing on the locality-based problems of Condition A and B in terms of anaphor and pronoun binding, the article claims that binding of an anaphor can be explained as an A’-phenomenon. The empty topic operator merges with the anaphor and moves to the C-domain. The stranded anaphor inside the clause is licensed by the empty operator via an A’-chain and the lexical antecedent of the anaphor plays no licensing role.